2011
DOI: 10.1063/1.3624587
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of CO oxidation reaction on Ir(111) surface at 33 ms resolution by means of wavelength-dispersive near-edge x-ray absorption fine structure spectroscopy

Abstract: The CO oxidation reaction on Ir(111) is observed by the near-edge x-ray absorption fine structure (NEXAFS) spectroscopy in the soft x-ray region. A continuous data acquisition at 33 ms real-time resolution is realized for a single event of the reaction without the repetition, by adopting the wavelength-dispersive NEXAFS technique. The time evolution of the coverages for atomic O and molecular CO is quantitatively estimated during the reaction. The obtained activation energy is significantly larger than that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Particularly, synchrotron-radiation-based electrondetecting core-level spectroscopies are quite useful because they are highly surface sensitive and they can provide information on structure and chemical states of both substrate and adsorbate. We have been using such techniques for in situ monitoring of prototypical catalytic surface reactions such as CO oxidation [9][10][11][12], NO reduction [13][14][15] and H 2 O formation [16][17][18] on metal surfaces under UHV conditions. For example, fast-XPS measurements for CO oxidation on Pd(1 1 1) revealed that phase transitions take place under a reaction condition and each oxygen phase exhibits a largely different reactivity and kinetics [10].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, synchrotron-radiation-based electrondetecting core-level spectroscopies are quite useful because they are highly surface sensitive and they can provide information on structure and chemical states of both substrate and adsorbate. We have been using such techniques for in situ monitoring of prototypical catalytic surface reactions such as CO oxidation [9][10][11][12], NO reduction [13][14][15] and H 2 O formation [16][17][18] on metal surfaces under UHV conditions. For example, fast-XPS measurements for CO oxidation on Pd(1 1 1) revealed that phase transitions take place under a reaction condition and each oxygen phase exhibits a largely different reactivity and kinetics [10].…”
Section: Introductionmentioning
confidence: 99%
“… Schematic of the dispersive NEXAFS technique. Adapted from reference with permission from the American Institute of Physics. …”
Section: Dispersive Nexafsmentioning
confidence: 99%
“…As we mentioned above, the dispersive NEXAFS technique can be applied to studies on catalytic surface reactions exhibiting relatively slow kinetics with a typical time scale of minutes. To improve the time resolution, we used a high‐flux beam from a new undulator beamline and a fast data collection system and achieved a data acquisition with the video rate (33 milliseconds/spectrum) . With this upgraded technique, we have studied relatively fast reaction kinetics on a model catalyst for an automobile exhaust gas: CO oxidation on an Ir surface at elevated temperatures close to realistic conditions.…”
Section: Dispersive Nexafsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, the surface O atoms are decreased due to the oxidation reaction with CO, and then CO molecules are increased by adsorption on the surface empty sites. The more recent development of ultrahigh-speed multichannel detector together with the use of the undulator beamline enables the acquisition of PES spectra in as short as 50 ms. 36) Another important development in time-resolved techniques other than PES, which should be added here, is fast NEXAFS spectroscopy 37) with time-resolution of 33 ms using a wavelength-dispersive technique. 38) The next approach to obtain better time-resolution than fast PES is to take an advantage of time-resolution of detectors such as a time-gated detector.…”
Section: )mentioning
confidence: 99%